Evaluating the students' experience with the Scrum Card Game: an experience report in a Software Engineering course - Moreira, Gabriel Gonçalves; Marques, Anna Beatriz dos Santos (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
The agile methodologies allow us to improve the software quality and achieve greater team productivity. However, due to time and resource constraints, there is a difficulty in simulating real scenarios of agile projects in the classroom and providing experiences in decision making and problem solving for the students. Educational games aim to reduce this challenge by simulating real software development experiences. Nevertheless, many educational games for teaching agile methodologies have no empirical evidence about the learning and experience promoted for students, or do not adopt an appropriate evaluation model. This paper reports an experience in a Software Processes class with 48 students playing the Scrum Card Game, a non-digital game that simulates activities of an agile project. We adopted the MEEGA+ model to evaluate the game regarding the students learning and experience with the game and Grounded Theory procedures to investigate the positives aspects and improve needs in relation to the game. From The results obtained, we observed that the game was positively evaluated by the students, being considered as a learning approach that allows practical experience with Scrum and development of secondary skills, such as collaboration, decision-making and problem solving.